Individual and family stress and crises - Weber, Janice G.; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2011)
Organized by stress model, this book helps readers understand the relationships among models, research, crisis prevention, and crisis management with individuals and families. Providing a balance of theory, research, hands-on applications, and intervention strategies, this innovative text presents a comprehensive overview of the field.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Stress (Psychology); Stress management; Family assessment; Adaptability (Psychology); Electronic books